Pemanfaatan Media Audio Visual dalam Pengenalan Huruf Hijaiyah pada Anak Kelompok B di TK Assalam - Esa Eryani; Imas Masitoh; Ai Teti Wahyuni; Aang Andi Kuswandi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The audio-visual media is a type of media that contains sound elements as well as images that can be seen, such as video recordings, various sizes of films, slides, sounds, and so on. This type of media is considered more attractive because it contains elements of both the first and second types of media. This study aims to describe how audio-visual media is used in teaching the Hijaiyah alphabet to children in Group B at Assalam Kindergarten. This research uses a descriptive method with a qualitative approach. The results show that a) in planning activities using audio-visual media in teaching the Hijaiyah alphabet to Group B at Assalam Kindergarten in Pagerbumi, teachers are accustomed to preparing lesson plans, learning media, learning methods, and the tools and materials used in learning activities. In addition to preparing lesson plans and learning media, teachers also stimulate children regarding what they should do in accordance with the theme being discussed; b) the implementation of learning with the use of audio-visual media in introducing Hijaiyah letters to Group B at Assalam Kindergarten Pagerbumi with the implementation of learning using audio media can improve children's ability to recognize Hijaiyah letters; c) The results of the learning evaluation using audio-visual media in introducing Hijaiyah letters in Katakana developed very well (BSB). In this case, children were able to recognize Hijaiyah letters and were able to name them.